Land rights & identity: the establishment of the Leliefontein Mission and its impact on the Little Namaqua of the Kamiesberg - Rawson, Kathryn (Department of Historical Studies, 2018)
This thesis attempts to provide an extensive historical narrative of the Kamiesberg region of Little Namaqualand in the Northern Cape of South Africa. In doing so it focuses on the indigenous occupants of the region, a group of Khoikhoi pastoralists known as the Little Namaqua. The Little Namaqua were few in number, but a people rich in cattle who occupied the area from the Groen Rivier in the south to the Buffels Rivier in the north for approximately the past 2000 years. Through the use of archaeological sources, written testimonies of 17th and 18th century travellers and the colonial archive this paper offers an in-depth analysis of both the pre-colonial and colonial occupation of the Kamiesberg. The patterns of transhumance adopted by the pre-colonial Little Namaqua were put under severe pressure at the dawn of the 18th century with the arrival of the first wave of European farmers known as 'trekboers'. Here, the Namaqua's notions of shared land-use and territoriality were confronted with the differing European perceptions of private land-ownership and property rights. Thus began the process of Namaqua displacement and land-encroachment at the hands of the trekboers who often settled around favourable watering points. This, paired with the ills of illegal cattle trading and the smallpox epidemic of 1722, resulted in both a cattless and a virtually landless Little Namaqua by the dawn of the 19th century. With few other alternatives, many enlisted into the workforce of European farmers or fled further north over the Orange River. Others instead opted for the protection afforded to them by a mission station. It is this group of Little Namaqua, those under Chief Wildschut, who form the basis of this research. By 1816 the Little Namaqua under Wildschut had invited the Wesleyan missionary, Barnabas Shaw, to establish a mission station at Leliefontein. The early years of the mission station, 1816-1850, were prosperous as both agricultural yields and livestock numbers increased rapidly. The latter half of the 19th century however saw the station in decline. This thesis argues that the virtually unprecedented move on the part of Wildschut and the Little Namaqua to invite a missionary to settle on their lands was a highly strategic one on the part of the Little Namaqua. The establishment of the station not only allowed them to hold onto land which would have otherwise been pilfered from them but it also provided them the necessary protection against the mischiefs of neighbouring farmers. Records suggest that the Little Namaqua were fullyaware of the consequences and benefits of this decision and thus this thesis posits that far from the victimised and marginalised people that history has moulded them to be, the Little Namaqua were instead a people with strategic foresight and thus should be credited with the agency that their actions necessitated.